Engineering Education for the 21st Century:Technology Based Hierarchical Online Learning - Ghosh, Avik W. (Journal of Engineering Education Transformations, 2016)
Engineering education in the 21st century faces a host of challenges. A new generation of students is finding itself perpetually wired, as brick and mortar buildings are competing with e-books, youtube and wikipedia, classrooms with gaming and Second Life, along with an overall push to decentralize education through Massive Open Online Courses (MOOCs) and virtual universities.We face a huge challenge and therein a unique opportunity to design platforms that can actively engage future engineers, teach useful skills and disseminate information for long-termed retention. With the proliferation of for-profit online universities like Univ. of Phoenix, and online courses by EdX, Coursera, Udacity, it is often hard to separate hope from hype when it comes to MOOCs and online learning. This paper focuses on my experiments with asynchronous and blended learning over years of engineering course design.